2021
DOI: 10.3390/jfmk6020048
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Induces Alternative Splicing of Neurexins in Frontal Cortex

Abstract: Aerobic exercise (AE) is known to produce beneficial effects on brain health by improving plasticity, connectivity, and cognitive functions, but the underlying molecular mechanisms are still limited. Neurexins (Nrxns) are a family of presynaptic cell adhesion molecules that are important in synapsis formation and maturation. In vertebrates, three-neurexin genes (NRXN1, NRXN2, and NRXN3) have been identified, each encoding for α and β neurexins, from two independent promoters. Moreover, each Nrxns gene (1–3) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 73 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Changes in Nrxn mRNA expression and alternative splicing are observed following in-vivo drug administration in nucleus accumbens ( Fuccillo et al, 2015 ) and globus pallidus ( Kelai et al, 2008 ). Modifications to the inclusion of SS4 are commonly observed in multiple brain regions following several experiences, including fear conditioning ( Rozic et al, 2011 ; Ding et al, 2017 ), stress ( Freire-Cobo and Wang, 2020 ), and exercise ( Innocenzi et al, 2021 ). In studies that distinguished multiple cell-types or brain regions, Nrxn expression profiles displayed cell-type and/or region-specific changes, suggesting that Nrxn expression profiles change in accordance with circuit-specific plasticity.…”
Section: Activity Dependent Neurexin Expressionmentioning
confidence: 99%
“…Changes in Nrxn mRNA expression and alternative splicing are observed following in-vivo drug administration in nucleus accumbens ( Fuccillo et al, 2015 ) and globus pallidus ( Kelai et al, 2008 ). Modifications to the inclusion of SS4 are commonly observed in multiple brain regions following several experiences, including fear conditioning ( Rozic et al, 2011 ; Ding et al, 2017 ), stress ( Freire-Cobo and Wang, 2020 ), and exercise ( Innocenzi et al, 2021 ). In studies that distinguished multiple cell-types or brain regions, Nrxn expression profiles displayed cell-type and/or region-specific changes, suggesting that Nrxn expression profiles change in accordance with circuit-specific plasticity.…”
Section: Activity Dependent Neurexin Expressionmentioning
confidence: 99%
“…Recent studies have shown that alternative splicing can be understood as an evolutionary adaptation to factors occurring an individual's life [1]. Moreover, a study by Innocenzi et al (2021) [2] based on transcriptome analyses, con rmed the occurrence of alternative splicing induced by an aerobic exercise in mice model. In humans, it has been shown that physical exercise can modify different isoforms of the genes encoding proteins crucial for skeletal muscle contraction [3].…”
Section: Introductionmentioning
confidence: 99%